2009
DOI: 10.1103/physrevb.80.235407
|View full text |Cite
|
Sign up to set email alerts
|

Surface energies, work functions, and surface relaxations of low-index metallic surfaces from first principles

Abstract: We study the relaxations, surface energies, and work functions of low index metallic surfaces using pseudopotential plane-wave density-functional calculations within the generalized gradient approximation. We study here the (100), (110), and (111) surfaces of Al, Pd, Pt, and Au and the (0001) surface of Ti, chosen for their use as contact or lead materials in nanoscale devices. We consider clean, mostly non-reconstructed surfaces in the slab-supercell approximation. Particular attention is paid to the converge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

82
317
1
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 460 publications
(414 citation statements)
references
References 84 publications
82
317
1
14
Order By: Relevance
“…(6), it was concluded that none of them improved on simply performing a very precise bulk and slab calculation. Recently Singh-Miller et al [14] came to the same conclusion when reviewing these different methods. The alternative methods are mainly useful when fine k meshing is unfeasible due to hardware limitations.…”
Section: B Dft Calculations For Surfacesmentioning
confidence: 72%
See 1 more Smart Citation
“…(6), it was concluded that none of them improved on simply performing a very precise bulk and slab calculation. Recently Singh-Miller et al [14] came to the same conclusion when reviewing these different methods. The alternative methods are mainly useful when fine k meshing is unfeasible due to hardware limitations.…”
Section: B Dft Calculations For Surfacesmentioning
confidence: 72%
“…The usefulness of DFT simulations therefore depends on their accuracy, i.e., the deviation with respect to experimental results. A number of studies have attempted to assess the accuracy of DFT-predicted surface properties [7][8][9][10][11][12][13][14][15][16][17][18]. Most of these studies, however, only consider a limited set of test surfaces, which brings into question the transferability and statistical significance of the accuracy estimate.…”
Section: Introductionmentioning
confidence: 99%
“…(110)) than for the close-packed surfaces (e.g., BCC(110) and FCC (111)). This result is due to the smoothing of the surface electric charge distribution (the Smoluchowski effect) that lowers the work function 28,44 . Moreover, it has been found empirically that a higher substrate work function usually leads to a lower MWF upon cesium adsorption 45 .…”
Section: Resultsmentioning
confidence: 99%
“…We find that a slab consisting of a minimum of four metal layers, where the two topmost layers are allowed to relax, is required for the work function to converge. A dipole correction is applied to compensate for the symmetry-breaking with respect to the fixed and free surface of the slab, reducing the number of layers needed compared to a full relaxation of the entire slab 28 . Figure 1 shows the typical dependence of the work function on the cesium coverage as observed both in experiments 20,29 and DFT simulations 19,30 .…”
Section: Methodsmentioning
confidence: 99%
“…Para fins de validação do modelo empregado nesse trabalho, foram selecionados três artigos da literatura que também utilizam o funcional GGA-PBE para os cálculos de superfície energia. [96][97][98] Os resultados para as superfícies comparadas apresentaram boa concordância com os resultados das superfícies disponíveis na literatura. O único caso em que se verificou um desvio foi o da superfície de Pt fcc(111), que apresentou uma diferença de −9,8% em relação à mesma superfície estudada por Da Silva et al 97 Em síntese, sabe-se que, quanto maior a energia de superfície, maior será a tendência da espécie metálica se deslocar para regiões internas do sólido.…”
Section: Discussão: Mecanismos De Formação De Nanoligasunclassified